Ins405AsnPro Mutation in the von Willebrand Factor Propeptide in Recessive Type 2A (IIC) von Willebrand’s Disease - Holmberg, L.; Karpman, D.; Isaksson, C.; Kristoffersson, A. C.; Lethagen, S.; Schneppenheim, R. (Thrombosis and Haemostasis, 1998)
The molecular defects of the von Willebrand factor (vWF) have been studied in the patient in whom the von Willebrand disease phenotype IIC was originally described. A six nucleotide insert, AATCCC, was found in exon 11 of the vWF gene, predicting the insertion of the amino acids asparagine and proline between phenylala-nine 404 and threonine 405 of the vWF propeptide. The mutation was present in one allele. Analysis of amplification products derived from platelet vWF mRNA showed the other allele to be silent. The patient is thus a compound heterozygote for a null allele and the IIC allele, in accord with the recessive mode of inheritance of the IIC phenotype. Family studies indicated the IIC mutation to have occurred de novo, possibly as a result of a duplication event. In vitro mutagenesis and expression in COS-7 cells confirmed the detrimental effect of the mutation on vWF multimer assembly. Taken together with those of earlier studies the present findings suggest that the IIC phenotype may well be exclusively caused by mutations which result in changes of the amino acid sequence in certain regions of the vWF propeptide. Although in the recently revised classification of von Willebrand’s disease variants, the IIC type is included in the 2A category, obviously it constitutes a very distinct subtype.